Therapeutic positioning of secretory acetylated APE1/Ref-1 requirement for suppression of tumor growth in triple-negative breast cancer in vivo - Lee, Yu Ran (Sci Rep, 2018)
Triple-negative breast cancer (TNBC) represents a relatively small proportion of all BCs but a relatively large proportion of BC-related death. Thus, more effective therapeutic strategies are needed for the management of TNBC. We demonstrated that the stimulation of apoptosis by the binding of secreted acetylated-apurinic apyrimidinic endonuclease 1/redox factor-1 (Ac-APE1/Ref-1) to the receptor for advanced glycation end products (RAGE) was essential for TNBC cell death in response to hyperacetylation. The aim of the present study was to assess the potential therapeutic efficacy of secretory Ac-APE1/Ref-1 in orthotopic TNBC xenografts in vivo. We found that hyperacetylation in xenografts caused secretion of Ac-APE1/Ref-1 into the blood, where the factor bound directly to RAGE in hyperacetylated tumor tissues. Hyperacetylation in the TNBC xenografts induced strong inhibition of tumor growth and development, leading to apoptotic cell death, accompanied by increased RAGE expression and generation of reactive oxygen species. Tissues exhibited markedly higher counts of apoptotic bodies, a reduced proliferation index, and reduced neovascularization compared with control tumors. Ac-APE1/Ref-1-stimulated apoptosis was markedly reduced in RAGE-knockdown tumors compared with RAGE-overexpressing tumors, even in the presence of hyperacetylation. The function of secreted Ac-APE1/Ref-1 was confirmed in other hyperacetylated TNBCs xenografts using BT-549 and MDA-MB-468 cells, demonstrating its relevance as an anti-cancer molecule.